Trading the VIX Futures Roll and Volatility Premiums with VIX Options. Issue 2 (6th May 2016) - Simon, David P.
Abstract : This study examines VIX option trading strategies based on the systematic tendencies of VIX futures from January 2007 through March 2014. The strategies involve buying VIX options to exploit the tendency of VIX futures to rise and fall when the VIX futures curve is in backwardation and in contango, respectively, as well as the tendency of VIX futures ex ante volatility premiums to spike and then revert to more typical levels. Subject to caveats about the often wide VIX option bid–ask spread quotes in the first few years of trading, the results demonstrate that these limited risk strategies are highly profitable. An important factor driving the results is that long VIX option strategies greatly benefit from a tendency of VIX option implied volatilities to rise with increases in the volatilities of underlying VIX futures contracts, as the latter move toward settlement and their volatilities converge to the typically higher volatility of the VIX. © 2016 Wiley Periodicals, Inc. Jrl Fut Mark 37:184–208, 2017